Analisis Tentang Kedisplinan Kerja Pegawai pada Kantor Camat Baturaja Timur Kabupaten Ogan Komering Ulu - Saleh, Rakhmat (Jurnal Publisitas, 2022)
The existence of the ranks of civil servants as state apparatus and public servants is very important to implement and organize the wheels of government and the wheels of development, therefore discipline is the key to the success of an organization in achieving its goals. Therefore, it is important to know how work discipline is and what factors hinder employee work discipline at the East Baturaja sub-district office, Ogan Komering Ulu district. This research is descriptive in nature which aims to describe, summarize various conditions, situations or variables that arise in the community that is the object of the research. The data collection technique used in this study used primary data in the form of observations and data sources, as well as secondary data in the form of interviews and documentation observations. The results of the study show that work discipline related to obedience to working hours has been going quite well, there are only a few parties who violate it with excuses. As for the variable of obedience to work procedures and obedience to the field of duty, it has been running as it should.